2006
DOI: 10.1177/0891988705284713
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Dementia Caregiver Desire to Institutionalize: Caregiver, Care Recipient, and Family Relationship Factors

Abstract: Several factors influence dementia caregiver desire to institutionalize; however, little is known about differences in caregivers who desire institutionalization versus those who do not. The current study compares predictors of desire to institutionalize in dementia caregivers. Seventy-two caregivers completed the Desire to Institutionalize Scale (DIS) and several psychosocial measures, including burden, dementia knowledge, self-efficacy, depression, health, care recipient daily functioning and memory/behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 29 publications
6
91
4
4
Order By: Relevance
“…Research has found that knowledge about dementia can in fact increase desire to institutionalise (DIS) the person with dementia, and so education alone may not be helpful in reducing caregiver burden 24 . There is increasing evidence showing that caregiver self-efficacy is a key factor in minimising burden 25 .…”
Section: Previous 'Informal' Researchmentioning
confidence: 99%
“…Research has found that knowledge about dementia can in fact increase desire to institutionalise (DIS) the person with dementia, and so education alone may not be helpful in reducing caregiver burden 24 . There is increasing evidence showing that caregiver self-efficacy is a key factor in minimising burden 25 .…”
Section: Previous 'Informal' Researchmentioning
confidence: 99%
“…Other than Chinese belief, family support and relationship for example husband helps in physical activities were very important in lifting the bed ridden demented patient which helps to reduce the caregiver physical burden. Poor family relationship resulting in poor social support was found to be a significant factor in determining the early institutionalization of dementia patients [18] . There was significant association between social support and caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for institutionalization include caregiver stress [40], burden [41], the behaviors of the care recipient [42], and ethnicity [43]. A meta-review of 782 studies which examined factors predicting nursing home placement for persons with dementia found that the greater emotional stress of the caregivers, a desire to institutionalize, and feelings of being "trapped" in care responsibilities increased the likelihood of placement [44].…”
Section: Desire To Institutionalizementioning
confidence: 99%